POLITICS OF LAW AND POWER IN THE COUNTRY OF INDONESIA - Muhamad Fadlan Rizkiawan; Aldo Permana Putra Susanto; Nazaruddin Lathif; Isep H Insan (Scholar Express Journals, 2021)
Law and power are two different things but influence each other. Law is a system of rules about human behavior. So the law does not refer to a single rule, but can be called a set of rules that make up a system. While strength is the ability of a person or a group to influence the behavior of another person or group, according to the desired behavior. the political configuration of a country will present the character of certain legal products in that country. In countries where the political configuration has a democratic character, the political product is responsive (populist), whereas in countries where the political configuration is characterized by authoritarianism, the legal product is orthodox (conservative/elistic). Changes in political configuration from authoritarian to democratic have an impact on changes in the character of legal products. A democratic political configuration will produce legal products. A democratic political configuration will produce responsive legal products, while an authoritarian political configuration will produce conservative legal products. Indonesia since the proclamation of independence on August 17, 1945 there has been a union between democratic political configurations and authoritarian political configurations, even though all of their constitutions stipulate democracy as one of the principles of living together in one country and a state.
Keywords: Law; Coercion; Politics